Stimulation of Hair Growth Effect by Fermented Ginsenosides Using Levilactobacillus brevis THK-D437 - Eun-Ji Yi; Trang Thi Minh Nguyen; Jeehaeng Jeong; Xiangji Jin; Qiwen Zheng; Se-Jig Park; Gyeong-Seon Yi; Su-Jin Yang; Tae-Hoo Yi (Fermentation)
Hair growth is crucial for physiological functions and psychological well-being, leading to an increasing demand for research in this area. While low-molecular ginsenosides have been shown to promote hair growth in mice, studies on their effects are limited, and there is a lack of research examining the impact of ginsenoside fermentation products derived from lactic acid bacteria. This study investigated the hair-growth-promoting effect of fermented ginsenoside by fermentation of Levilactobacillus brevis THK-D437, which was isolated from the traditional Korean fermented food kimchi and features high β-glucosidase activity. In the cell-based MTT assay, the proliferation rate was increased by 25% in the fermented ginsenoside-treated group on human hair dermal papilla cells (HHDPCs). In the alopecia mouse model study (C57BL/6 mouse model), enhanced hair growth was observed in the fermented ginsenoside-treated mouse groups. Tissue histological analyses showed that the number of hair follicles and the thickness of the epidermis, respectively, were increased in the fermented ginsenoside-treated mouse groups. These results suggested that fermented ginsenoside has a promoting effect on hair growth and a retarding effect on the catagen stage. Therefore, fermented ginseng products might be a new potential therapeutic candidate for promoting hair growth.